THE ROLE OF INTERFERON PREPARATIONS IN THE TREATMENT OF ACUTE VIRAL RESPIRATORY INFECTIONS IN INFANTS, BABIES AND TODDLERS (RESULTS OF A MULTICENTER COMPARATIVE RANDOMIZED CLINICAL TRIAL) - L.V. Feklisova; A.V. Gorelov; V.P. Drinevskii; A.A. Ploskireva; E.V. Tselipanova; E.Yu. Shvets; E.V. Kanner; Yu.N. Lin'kova; E.V. Chernyaeva (Union of pediatricians of Russia, 2011)
The paper analyzes the results of a comparative clinical trial of drugs recombinant human interferon alpha-2b in the dosage form of suppositories for their use in the treatment of ARVI in infants, babies and toddlers age. In accordance to the selection criteria 100 children who were hospitalized, aged from 6 months to 3 years with clinically diagnosed ARVI were included in the study. Two study groups were formed: basic, which patients within 5 days received suppositories containing taurine and interferon alpha (125,000 IU),  and the comparison group, where patients received suppositories with interferon (150,000 IU). The patients of both groups were subjects of medical observation for 5 days with an estimate of the effectiveness of treatment on the 6th day of therapy. The eliminating activity of the exploring drugs was determined using standard laboratory techniques (PCR or DFA scrapings from the nasopharynx). The study established the high effectiveness and wide safety profile of both drugs. No cases of the adverse events that have established link with the study medications. Key words: influenza, ARVI, recombinant human interferon alpha-2b, taurine, suppositories, children. (Pediatric Pharmacology. - 2011; 8 (5): 76-82.)